Synthesis of 3- and 29-substituted celastrol derivatives and structure-activity relationship studies of their cytotoxic activities. Issue 15 (1st August 2017) - Shan, Wei-Guang; Wang, Han-Guang; Chen, Yan; Wu, Rui; Wen, Yan-Tao; Zhang, Li-Wen; Ying, You-Min; Wang, Jian-Wei; Zhan, Zha-Jun
Graphical abstract: Abstract: A series of 3-carbamate and 29-ester celastrol derivatives (compounds1 –26 ) were designed and synthesized. These analogues were evaluated for their cytotoxic activities against several cancer cell lines. Cytotoxicity data revealed that the properties of substituents and substitution position had important influence on cytotoxic activity. Modification of C-3 hydroxyl with size-limited groups did not reduce the activity obviously. The introduction of polarity group like piperazine could improve the solubility. Compound23 was chosen to further evaluate anti-tumor efficacy in vivo . It showed higher inhibition rate and better safety than celastrol during in vivo experiment by intragastric administration. The preliminary antitumor studies of compound23 in vivo showed that it might be promising for the development of new antitumor agents.